The Impact of Radical Cystectomy and Urinary Diversion on Suicidal Death in Patients With Bladder Cancer. Issue 2 (March 2016) - Klaassen, Zachary; DiBianco, John M.; Jen, Rita P.; Harper, Benjamin; Yaguchi, Grace; Reinstatler, Lael; Woodard, Cynthia; Moses, Kelvin A.; Terris, Martha K.; Madi, Rabii
Abstract : PURPOSE: Compared to the general population, suicide is more common in the elderly and in patients with cancer. We sought to examine the incidence of suicide in patients with bladder cancer and evaluate the impact of radical cystectomy in this high-risk population. METHODS: Patients diagnosed with urothelial carcinoma from 1988 to 2010 were identified in the Survey, Epidemiology, and End Results (SEER) database. Contingency tables of suicide rates and standardized mortality ratios (SMRs) and 95% confidence intervals were calculated. Multivariable logistic regression models were performed to generate odds ratios (ORs) for the identification of factors associated with suicide in this population. RESULTS: There were 439 suicides among patients with bladder cancer observed for 1, 178, 000 person-years (Standard Morbidity Ratio [SMR] = 2.71). All demographic variables analyzed had a higher SMR for suicide compared to the general population, in particular age ≥80 years (SMR = 3.12), unmarried status (SMR = 3.41), and white race (SMR = 2.60). The incidence of suicide was higher in the general population for patients who underwent radical cystectomy compared to those who did not (SMR = 3.54 vs SMR = 2.66). On multivariate analysis, the strongest predictors of suicide were male gender (vs female; OR = 6.63) and distant disease (vs localized; OR = 5.43). CONCLUSIONS: Clinicians should be aware of risk factors for suicide in patients diagnosed with bladder cancer, particularly older, white, unmarried patients with distant disease, and/or those who have undergone radical cystectomy. A multidisciplinary team-based approach, including wound ostomy care trained nursing staff and mental health care providers, may be essential to provide care required to decrease suicide rates in this at-risk population.